Inovasi Pengembangan Media Pembelajaran Interaktif Berbasis Aplikasi Canva Premium dan CapCut Premium IPAS di Sekolah Dasar: Penelitian - Kiki Fajariani; Khairunnisak (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Innovation in the development of learning media is essential to improve the quality of the teaching and learning process, especially in the Natural and Social Sciences (IPAS) subject at the elementary school level. This study aims to describe the development and implementation of interactive learning media based on Canva Premium and CapCut Premium applications in IPAS learning at SD Negeri 1 Jangka. The learning media were developed by combining attractive visual designs, animations, instructional videos, and supporting audio tailored to the characteristics of elementary school students. The method used was learning media development through the stages of planning, production, implementation, and evaluation. The results of the implementation indicate that the use of Canva Premium and CapCut Premium can increase students’ learning interest, motivation, and understanding of IPAS materials. Students become more active in the learning process as the materials are presented visually, interactively, and contextually. In addition, teachers are greatly assisted in delivering learning materials in a more creative and innovative manner. Therefore, interactive learning media based on Canva Premium and CapCut Premium are feasible to be used as an innovative alternative in IPAS learning at the elementary school level to create enjoyable, effective, and meaningful learning experiences.